Pembaruan Hukum Islam di Indonesia - Ismail, Ismail (TAJDID, 2019)
In the early days of the entry of Islam in Indonesia the emphasis of Islamic teachings on legal aspects was not as strong as it is now. From the historical record, Islam that developed in Indonesia in the early days was very oriented towards tasawuf. This is because Islamic tasawuf who came to the archipelago, in certain aspects "fit" with the background of the local community influenced by Hindu-Buddhist asceticism and syncretism of local beliefs. In the next stage, Islam is oriented to Sufism, gradually becoming more oriented towards shari'ah. This change in orientation was partly due to a process of renewal or refinement that began in the 17th century and continues today. The Islamic law developing in Indonesia nowadays has got much changing from its origin, syafi’iyah to moderate. The modernity of Islamic law that take long time is provable by appearing of the national fiqh mazhab (religious sect). To get the better understanding on the happening process, the writer will divide into two periods of modernity. First is the initial period indicated by having ijtihad and self-releasing on taklid or fanatic attitude to a certain mazhab. The Second period load the effort to bear the mazhab that is suitable to the national personality. This is called National mazhab later.